Recent advances in the biosynthesis and production optimization of gentamicin: A critical review - Feng Xu; Kaihao Hu; Ali Mohsin; Jie Wu; Lihuan Su; Yuan Wang; Rong Ben; Hao Gao; Xiwei Tian; Ju Chu (Synthetic and Systems Biotechnology)
Gentamicin, an aminoglycoside antibiotic, is generated by a few species within the genus Micromonospora and has garnered significant attention due to its broad-spectrum efficacy in combating numerous infectious diseases. Comprising a complex array of closely related aminoglycoside compounds, the gentamicin B and C complexes emerge as particularly pertinent in clinical contexts. This review outlines the latest advancements in the biosynthesis and production of gentamicin, commencing with a comprehensive overview of its biosynthetic pathway. Subsequently, the article encapsulates a spectrum of strategies currently deployed to augment gentamicin yields. These strategies include mutation screening, molecular biological techniques, and optimization of the fermentation process. Moreover, numerous methods have been documented for detecting gentamicin across a range of matrices, underscoring the significance of precise quantitative analysis. Finally, the review furnishes an exhaustive market analysis and future outlook, elucidating prevailing trends and challenges within the gentamicin industry. Overall, this article serves as a pivotal resource for researchers and professionals engaged in gentamicin research, furnishing a meticulous introduction to efficient synthesis technologies and diverse applications, alongside presenting innovative concepts and methodologies aimed at increasing gentamicin production.